Pashia, Eleni - (:unkn) unknown (My University, 2026)
Dr Eleni Pashia is an architect, researcher and educator. She is currently a Research Associate at the Cyprus University of Technology coordinating multiple tasks on the topics of Inclusiveness and Embeddedness in Higher Education and Research. She is also a co-instructor of the MSc Interaction Design offered by the Cyprus University of Technology and the Tallinn University. Eleni is also an Associate Trainer, Researcher and Mentor to several organizations in Cyprus on the topics of Peace Education and Gender History, as well as Inclusion and Entrepreneurship. Eleni’s interests are focused on the intersections of Design Thinking and Space with the topics of Gender Equality, Inclusion, Diversity and Intersectionality. She has experience in designing and facilitating critical, experiential and participatory workshops and events, and in writing, editing and designing educational material and scientific publications. Eleni studied Architecture Engineering at the Polytechnical School of Patra in Greece (first & excellent), and holds a PhD in Architecture from the Faculty of Social Sciences at the University of Sheffield in UK (full departmental scholarship).